The Idea of Awakening: Giorgio Agamben and the Nāgārjuna References - DeCaroli, Steven (Res Publica. Revista de Historia de las Ideas Políticas, 2015)
This essay discusses the distinction and the basic dilemma of constituting power and constituted power. The predicament encountered in keeping these two concepts theoretically distinct repeats the problem embedded in the paradox of sovereignty which Agamben has placed at the centre of his political inquiry. Around this problem, we can explain the relation between Agamben and Carl Schmitt and, following the Negri’s thesis, the shift from the politics to the ontology. The movement from politics to ontology opens a pathway for reconsidering the relation between actuality and potentiality, the central feature of Agamben’s philosophy. Once at this point, this paper proposes a not obvious link between Agamben and Buddhism.